2021
DOI: 10.1140/epjc/s10052-021-09585-9
|View full text |Cite
|
Sign up to set email alerts
|

Charged stars in 4D Einstein–Gauss–Bonnet gravity

Abstract: An alternative gravity theory that has attracted considerable attention recently is the novel four-dimensional Einstein–Gauss–Bonnet (4EGB) gravity. This idea was proposed to bypass the Lovelock’s theorem and to permit nontrivial higher curvature effects on the four-dimensional local gravity. In this approach, the Gauss–Bonnet (GB) coupling constant $$\alpha $$ α is rescaled by a factor of $$\alpha /(D -4)$$ α / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…It is relevant to mention that some of us had recently calculated new traversable wormhole families of solutions in ffalse(Qfalse)$f(Q)$ [ 81,82 ] by using the embedded spacetime and non‐commutative geometry within the conformal symmetry. Later, Banerjee and his coauthors [ 83 ] systematically studied the field equations for wormhole solutions and found the violation of null energy conditions in the throat neighborhood. Recently, Sharma and Mishra [ 84 ] have discussed the traversable wormhole solutions with non‐exotic fluid in ffalse(Qfalse)$f(Q)$ gravity.…”
Section: Introductionmentioning
confidence: 99%
“…It is relevant to mention that some of us had recently calculated new traversable wormhole families of solutions in ffalse(Qfalse)$f(Q)$ [ 81,82 ] by using the embedded spacetime and non‐commutative geometry within the conformal symmetry. Later, Banerjee and his coauthors [ 83 ] systematically studied the field equations for wormhole solutions and found the violation of null energy conditions in the throat neighborhood. Recently, Sharma and Mishra [ 84 ] have discussed the traversable wormhole solutions with non‐exotic fluid in ffalse(Qfalse)$f(Q)$ gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Invoking the partial waves approach Lima Junior et al [38] showed that the cross-section of planar scalar massless waves are impacted by the GB coupling constant in 4D EGB. Charged stars, [39] wormholes, [40] gravitational lensing, [41] isotropic perfect fluids [42] and Born-Infeld BHs [43] have been investigated recently. Wang and Ge [44] considered the coupling of 4D EGB-charged BHs with a scalar field.…”
Section: Introductionmentioning
confidence: 99%
“…The Kaluza-Klein reduction method of the limit D → 4 yields a special class of scalar-tensor theories in the Horndeski family [97,98]. Similar method was used in [88,99,100] by adding a counter term in D-dimensions and then taking D → 4 limit. Furthermore, many projects have been analyzed the previous issues coming from the new 4-dimensions EGB gravity.…”
Section: Introductionmentioning
confidence: 99%